Interventional Cardiologists’ Worst Enemy: The Plant-Based Diet Revolution - Mulijono, Dasaad (Cardiology and Cardiovascular Medicine, 2025)
Despite overwhelming scientific evidence demonstrating the ability of a Plant-Based Diet (PBD) to prevent and even reverse coronary artery disease (CAD), the field of interventional cardiology remains stubbornly fixated on invasive procedures and pharmacological treatments. This resistance persists primarily due to entrenched financial incentives, professional prestige, and a medical culture favouring procedural complexity over preventive simplicity. This provocative article critically examines the systemic barriers preventing widespread adoption of PBD within interventional cardiology, arguing that the real "enemy" is not CAD itself, but rather a healthcare model fundamentally misaligned with patient-centric, preventive medicine. By integrating Artificial Intelligence (AI) with rigorous nutritional science, Bethsaida Hospital, under the pioneering leadership of Prof. Dasaad Mulijono, presents a groundbreaking blueprint for the future of cardiovascular care. At Bethsaida, the combined use of Drug-Coated Balloon (DCB) therapy and personalized PBD has yielded clinical outcomes previously deemed unattainable—remarkably low restenosis rates, substantial regression of coronary plaques, medication reduction, and reversal of chronic diseases. Prof. Mulijono’s innovative strategy effectively challenges the prevailing interventional paradigm, demonstrating that it is both clinically feasible and ethically imperative to shift towards a dietcentred, AI-enhanced model of cardiovascular medicine. As AI-driven analytics continue to elucidate the undeniable efficacy of plant-based nutrition, traditional interventional cardiology faces an existential threat: adapt and evolve or risk obsolescence. The profound successes achieved at Bethsaida Hospital underscore the power of diet as medicine and highlight a pressing ethical and economic imperative for systemic transformation. The future of cardiology demands a revaluation of professional priorities, placing compassionate, preventive care above procedural profit. Thus, the PBD revolution emerges not as an enemy but as a catalyst to reclaim the heart of medicine.